OPTIMIZING ONLINE CHANNELS: EXPLORING THE INTERPLAY OF E-COMMERCE IN CUSTOMER JOURNEY OF SMARTPHONE & GADGET RETAIL - Edward Ransoen, Yosua
The growth of e-commerce has changed the retail industry all over the world in all product segments, and the smartphone & gadget is no exception. Over the past years, e-commerce platforms in Indonesia have grown rapidly as convenience to shopping for products. However, Smartphone Brand still faces the huge issue on the Online Market. After the post pandemic era, the number of market share of Online Market keeps decreasing due to customers still prefer to buy the product through Offline Store. This research objective is to analyse e-commerce and customer journey in the context of Handphone & Gadget purchases. It seeks to explore the factors that drive consumers to buy the products in E-Commerce compared to Offline Market & offering insights and recommendations for Smartphone Manufacturers Company & E-Commerce Platform to grow the Online Market & Expand the audiences. The study addresses key questions about consumer behavior: What motivates people to buy smartphones and gadgets online rather than in-store? How do they perceive their online shopping experience, and what factors affect their satisfaction? What obstacles do they face when shopping online, and how do they overcome them? How do they react to personalized marketing and recommendations? And what drives their loyalty and repeat purchases in the online market? The study using Customer Decision Journey, Marketing Technology, and Porter Five Forces analysis as Theoretical Foundation to analyze & develop strategies. From these studies, key factors that influence consumers come from Delivery, Promotion, Store Information, & Simplicity to find information. This study will provide business solution & implementation plan that will become insight & recommendation for Smartphone Manufacturers Company & E-Commerce Platform to navigate the business issue